Sovereignty disavowed: the Tupac Amaru revolution in the Atlantic world. Issue 3 (2nd July 2016) - Thomson, Sinclair
ABSTRACT: While the Andean insurrection of the early 1780s, most often associated with the Inka leader Tupac Amaru II, was the most powerful challenge to Spanish rule in colonial Latin America, it is generally ignored in the Atlantic historiography of the Age of Revolution. This article reviews the reasons for this neglect and traces the problem back to the late eighteenth and early nineteenth centuries. It demonstrates for the first time that knowledge of the revolution in the Andes circulated widely throughout the Atlantic world in the early 1780s. It also provides evidence of a deep panic on the part of Spanish authorities, who feared that the anti-colonial revolution unfolding in British North America could find a counterpart in Spanish South America, especially with instigation by their British imperial rivals. It reveals Spanish attempts to prevent circulation of the news of the insurrection and the beginnings of a tradition that would reduce the meaning of the Andean revolution to an expression of race war. It argues more generally that this case of "silencing" (M. R. Trouillot) and "disavowal" (S. Fischer) in the Atlantic world reflected a repudiation of the radical principle of indigenous political sovereignty which underlay the Andean insurgencies. Rather than incorporate the Andean case into the existing paradigm of Atlantic revolutions, the article seeks to enrich the historiography of the Age of Revolution by showing that projects for indigenous territory and political authority, which challenged European and creole sovereignty in the Americas, deserve to be seen as integral to the epoch.